1983
DOI: 10.1038/bjc.1983.268
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroid receptor proteins in foetal, adult and malignant human liver tissue

Abstract: Summary Sex steroid receptor proteins were studied in human normal liver and hepatocellular carcinoma (HCC). Oestrogen receptor (ER) was detected in nucleosol and cytosol of 4 normal adult and 5 malignant liver specimens and in the cytosol of 6 foetal liver samples. Levels were 27.6-500 fmol mg 1 soluble protein in normal adults (Kd 1.48 x l0-8-l.l2 x 1010moll-1), 45-290fmolmg-1 in malignant liver tissue (Kd 3.26x 10-9-3.64x 10-'moll-1) and a mean of 93fmolmg-1 in foetal tissue (Kd 1.55x lO-9moll-P). Androgen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…In 1978, Duffy and Duffy first reported the presence of ER in normal human liver [28] . Subsequently, the presence of ERs in human HCC was demonstrated by Molteni et al [29] followed by Friedman et al [30] and Iqbal et al [31] . Since then, a number of studies have been reported addressing the expression of ERs in normal as well as neoplastic liver tissues.…”
Section: Estrogen Receptormentioning
confidence: 99%
“…In 1978, Duffy and Duffy first reported the presence of ER in normal human liver [28] . Subsequently, the presence of ERs in human HCC was demonstrated by Molteni et al [29] followed by Friedman et al [30] and Iqbal et al [31] . Since then, a number of studies have been reported addressing the expression of ERs in normal as well as neoplastic liver tissues.…”
Section: Estrogen Receptormentioning
confidence: 99%
“…Regardless of the etiology, chronic liver diseases progress at unequal rates in the two sexes, with the major sequelae, such as cirrhosis and HCC, being more common in men than in women (16,54). The significance of androgen receptor (AR) expression in HCC and the surrounding liver has been studied extensively (18,31,33). With this background, we decided to investigate the relationship between AR and HCC after HCV infection, knowing that human liver expresses both estrogen receptors and ARs.…”
mentioning
confidence: 99%
“…The stimulatory effect on fetal hepatocyte proliferation may be due to the direct action of estrogen receptors present in fetal hepatocytes (PASQUALINI, SUMIDA and GELLY, 1976;IQBAL et al, 1983;LAX et al, 1983). An increase in RNA polymerase activity by estrogens may be a possible trigger for hepatocyte proliferation, as has been reported for the uterus (CLARK and PECK, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…E3 is the most potent stimulant of hepatocyte proliferation among these three natural estogens (FUJII, HAYAMA and KOTANI,1985). Estrogen receptors are known to exist in the fetal liver cells of various species (PASQUALINI, SUMIDA and GELLY, 1976;IQBAL et al, 1983;LAX et al, 1983). Therefore, in the present study, fetal mouse livers were transplanted beneath the kidney capsule of adult hosts and E3 was administered to ascertain its possible physiological role in the growth of the fetal liver.…”
mentioning
confidence: 99%